Cover Image, Volume 41, Issue 26. Issue 26 (17th August 2020) - Raucci, Umberto; Perrella, Fulvio; Donati, Greta; Zoppi, Maria; Petrone, Alessio; Rega, Nadia
Abstract : The cover image is based on the Original Article Ab‐initio molecular dynamics and hybrid explicit‐implicit solvation model for aqueous and non aqueous solvents: GFP chromophore in water and methanol solution as case study by Nadia Rega, Alessio Petrone, Fulvio Perrella et al., https://doi.org/10.1002/jcc.26384